Chapter 10: Approaches to minimum-income protection in old age: comparing the three Scandinavian countries (Edward Elgar Publishing, 2021)
This chapter offers a comparative study of the current minimum income protection schemes for old age pensioners in Denmark, Norway and Sweden. The primary purpose is to describe and assess developments in the overall generosity of minimum protection provided through the pension system proper and other relevant instruments. It is shown that the Danish and Norwegian systems of minimum protection have remained comparatively generous, while the level of minimum protection offered to old age pensioners in Sweden is significantly lower. This is confirmed by the observation of significantly higher levels of financial poverty among the elderly in Sweden compared to Denmark and Norway. It is argued that deciding on the level of minimum protection and designing its interplay with earnings-related, contributory pensions poses policy makers with an intricate dilemma between reducing old age poverty and maintaining a strong link between previous earnings/contributions and old age benefits.